Balanitis circinata as the sole clinical presentation of underlying sexually acquired reactive arthritis: A case report - Sharma, Loknandini; Das, Niyor Mukta; Nachiketa, Nachiketa (Indian Journal of Case Reports, 2024)
A 35-year-old male was diagnosed with a case of HLA27-positive reactive arthritis post-evaluation. He presented with the only symptoms of recurrent genital ulcers on glans penis of 4 months duration. The patient was treated with nonsteroidal anti-inflammatory drugs, a short course of systemic steroids, and a local immunomodulator cream on the penile lesion. The patient responded well to the treatment and returned to his usual life activities with no occurrence so far.